Rothamsted International - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Rothamsted Experimental Station in England, since its foundation in 1843, has established an international reputation that is built on many important contributions to UK and world agriculture. In particular, Rothamsted is renowned for its pioneering...